Titanium nitride-based self-release molybdenum disulfide lubricating composite film as well as preparation method and application thereof
By introducing a porous structure into the TiN film and filling it with molybdenum disulfide, a titanium nitride-based self-releasing molybdenum disulfide lubricated composite film was prepared, which solved the problems of high friction coefficient and weak MoS2 adhesion of the TiN film, and achieved low friction and high load-bearing performance under environmental transition conditions.
Patent Information
- Application Number
- CN202510075034.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
AI Technical Summary
The existing TiN films have a high coefficient of friction, which limits their application in the field of lubrication and friction reduction, and the weak adhesion and poor oxidation resistance of MoS2 to the substrate shorten their service life.
A porous titanium nitride film was prepared on the substrate surface by magnetron sputtering technology, and a molybdenum disulfide precursor was filled with a molybdenum disulfide precursor by immersing in an aqueous solution of molybdenum and sulfur sources, and then subjected to reducing heat treatment to obtain a titanium nitride-based self-releasing molybdenum disulfide lubricated composite film.
In the environment of relative humidity transition, the titanium nitride-based self-release molybdenum disulfide lubricated composite film can maintain a low coefficient of friction and provide continuous friction reduction lubrication effect.
Smart Images

Figure CN119843232A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lubricating coatings, and in particular to a titanium nitride-based self-releasing molybdenum disulfide lubricating composite film and a preparation method and application thereof. Background Art
[0002] One of the main challenges facing contemporary space coating technology is how to achieve low friction and high load-bearing capacity in the transition between low and high temperature environments to protect precision mechanical parts. Among the numerous coating systems, TiN (Titanium nitride) is a new industrial material with high hardness, high wear resistance, high chemical and thermodynamic stability, and high load-bearing capacity. It is the first industrialized and widely used hard film material. TiN film is used as a protective and decorative coating in mold devices, metal surface protection, automobiles, aerospace and other fields. However, TiN film has a high friction coefficient, which limits its application in the field of lubrication and friction reduction. MoS2 (Molybdenum (IV) sulfide) is a solid lubricant with a low friction coefficient. It is widely used in the fields of mechanical parts such as aerospace, nuclear power, etc. to reduce their energy loss and wear loss. However, the weak adhesion of MoS2 to the substrate and its poor oxidation resistance shorten its service life, limiting the use of MoS2 in the transition between dry and wet environments.
[0003] Based on the problems of TiN and MoS2, researchers have increased the hardness and density of the film by doping multiple phases or multi-layer design to reduce friction, improve the wear resistance of the film and reduce the friction coefficient of the film. However, this method has certain limitations. Since the melting points of the co-deposited phases are different, the deposition rates of each phase are different during the deposition process, making it difficult to control the structure and performance of the coating. Therefore, it is of great significance to prepare a coating with excellent structure, high load-bearing performance, and low friction after environmental changes. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a titanium nitride-based self-releasing molybdenum disulfide lubricating composite film and its preparation method and application. The titanium nitride-based self-releasing molybdenum disulfide lubricating composite film prepared by the preparation method of the present invention can maintain a low friction coefficient in an environment with relative humidity changes.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a titanium nitride-based self-releasing molybdenum disulfide lubricating composite film, comprising the following steps:
[0007] A porous titanium nitride film is prepared on the surface of a substrate by magnetron sputtering with titanium metal as a target; the angle between the normal line of the substrate and the normal line of the target is 80-89°;
[0008] Soaking the porous titanium nitride film in an aqueous solution of a molybdenum source and a sulfur source to obtain a titanium nitride film filled with a molybdenum disulfide precursor;
[0009] The titanium nitride film filled with the molybdenum disulfide precursor is subjected to reduction heat treatment to obtain the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film.
[0010] Preferably, during the magnetron sputtering process, the working gases are argon and nitrogen.
[0011] Preferably, the conditions for the magnetron sputtering are: the straight-line distance between the target material and the substrate is 100-200 mm, the pressure of the working gas is 0.2-1.0 Pa, the flow rate of argon is 100-400 sccm, the flow rate of nitrogen is 50-200 sccm, the target current is 5-12 A, the deposition time is 100-150 min, and the deposition temperature is 303-573 K.
[0012] Preferably, the aqueous solution of the molybdenum source and the sulfur source is an aqueous solution of ammonium tetrathiomolybdate;
[0013] The concentration of the aqueous solution of ammonium tetrathiomolybdate is 10 to 30 mg / mL.
[0014] Preferably, the immersion is carried out under ultrasonic conditions;
[0015] The number of ultrasonic treatments is 2 to 5 times; the duration of each ultrasonic treatment is 40 to 60 minutes.
[0016] Preferably, the reduction heat treatment is carried out under the condition of nitrogen and hydrogen;
[0017] The flow rate of the nitrogen gas is 40 to 80 sccm, and the flow rate of the hydrogen gas is 20 to 40 sccm.
[0018] Preferably, the reduction heat treatment is carried out at a temperature of 300 to 450° C. and for a time of 40 to 80 minutes.
[0019] Preferably, before preparing the porous titanium nitride film, the method further comprises preparing a titanium transition layer on the surface of the substrate.
[0020] The present invention also provides a titanium nitride-based self-releasing molybdenum disulfide lubricating composite film prepared by the preparation method described in the above technical solution, comprising a porous titanium nitride film and molybdenum disulfide filled in the pore structure of the porous titanium nitride film;
[0021] The pore structure of the porous titanium nitride film is a submicron-level pore structure.
[0022] The present invention also provides the application of the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film described in the above technical solution in the field of lubricating coatings.
[0023] The invention provides a method for preparing a titanium nitride-based self-releasing molybdenum disulfide lubricating composite film, comprising the following steps: adopting magnetron sputtering and taking titanium metal as a target material to prepare a porous titanium nitride film on the surface of a substrate; the angle between the normal line of the substrate and the normal line of the target material is 80-89 degrees; immersing the porous titanium nitride film in an aqueous solution of a molybdenum source and a sulfur source to obtain a titanium nitride film filled with a molybdenum disulfide precursor; and performing a reduction heat treatment on the titanium nitride film filled with the molybdenum disulfide precursor to obtain the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film. The preparation method of the present invention introduces submicron pores in the titanium nitride film by performing oblique angle deposition (controlling the angle between the normal line of the substrate and the normal line of the target material), and introduces molybdenum disulfide into the submicron pores by immersion. Since molybdenum disulfide is a lubricating phase and can maintain a low friction coefficient, the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film can be in an environment where the relative humidity changes. During the friction process, on the one hand, the coating is continuously worn, and the molybdenum disulfide in the pores is naturally released to the friction contact surface. On the other hand, due to the pressure during the sliding process, the molybdenum disulfide in the pores can be released to the friction contact surface, so that the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film continuously releases molybdenum disulfide to the friction contact surface, maintains a low friction coefficient, and provides a friction-reducing lubrication effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The surface SEM image (a) and the cross-sectional SEM image (b) of the porous titanium nitride film described in Example 2 and the surface SEM image (c) and the cross-sectional SEM image (d) of the dense titanium nitride film described in Comparative Example 1;
[0025] Figure 2 The friction coefficient curve of the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film described in Example 2 when the relative humidity changes from 20% to 70%;
[0026] Figure 3 This is the friction coefficient curve of the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film described in Comparative Example 1 when the relative humidity changes from 20% to 70%. DETAILED DESCRIPTION
[0027] The present invention provides a method for preparing a titanium nitride-based self-releasing molybdenum disulfide lubricating composite film, comprising the following steps:
[0028] A porous titanium nitride film is prepared on the surface of a substrate by magnetron sputtering with titanium metal as a target; the angle between the normal line of the substrate and the normal line of the target is 80-89°;
[0029] Soaking the porous titanium nitride film in an aqueous solution of a molybdenum source and a sulfur source to obtain a titanium nitride film filled with a molybdenum disulfide precursor;
[0030] The titanium nitride film filled with the molybdenum disulfide precursor is subjected to reduction heat treatment to obtain the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film.
[0031] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0032] The invention adopts magnetron sputtering and uses titanium metal as a target material to prepare a porous titanium nitride film on the surface of a substrate; the angle between the normal line of the substrate and the normal line of the target material is 80-89 degrees.
[0033] In the present invention, before preparing the porous titanium nitride film, it is preferred to prepare a titanium transition layer on the surface of the substrate.
[0034] Before preparing the titanium transition layer, the present invention also preferably includes cleaning and drying the substrate in sequence. In the present invention, the cleaning is preferably ultrasonically cleaned in acetone for 15 minutes and ultrasonically cleaned in anhydrous ethanol for 5 minutes. The present invention does not have any special restrictions on the drying process, and the drying process can be carried out using a process well known to those skilled in the art.
[0035] The present invention has no special limitation on the material of the substrate, and any material familiar to those skilled in the art (such as M2 high-speed steel or 304 stainless steel) can be used. In an embodiment of the present invention, the material of the substrate can be 304 stainless steel.
[0036] In the present invention, the method for preparing the titanium transition layer is preferably magnetron sputtering; before performing the magnetron sputtering, the substrate is preferably glow discharged cleaned in a high-purity argon atmosphere; the flow rate of the high-purity argon is preferably 800sccm; the bias voltage of the glow discharge cleaning is preferably -1000V, and the time of the glow discharge cleaning is preferably 30min.
[0037] In the present invention, during the preparation of the titanium transition layer, the flow rate of argon gas is preferably 300-400sccm, more preferably 400sccm, the current passed inside the deposition target is preferably 6-8A, more preferably 8A; the time is preferably 2-7min, more preferably 5min, and the deposition temperature during the deposition process is preferably 303-573K, more preferably 303K or 573K.
[0038] In the present invention, the thickness of the titanium transition layer is preferably 100-200 nm.
[0039] In the present invention, the titanium transition layer can enhance the bonding force between the substrate and the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film.
[0040] In the present invention, the angle between the normal line of the substrate and the normal line of the target is 80-89°, preferably 85°. In an embodiment of the present invention, the angle between the normal line of the substrate and the normal line of the target can be 85°.
[0041] In the present invention, during the magnetron sputtering process, the working gas is preferably argon and nitrogen.
[0042] In the present invention, the target material is titanium metal, and the titanium metal is preferably high-purity titanium metal; the purity of the high-purity titanium metal is preferably ≥ 99.7%. In an embodiment of the present invention, the high-purity titanium metal can be a rectangular metal target with a purity of 99.7%.
[0043] In the present invention, during the magnetron sputtering process, the working gases are preferably argon and nitrogen; the flow rate of the argon is preferably 100 to 400 sccm, more preferably 200 to 300 sccm; the flow rate of the nitrogen is preferably 50 to 200 sccm, more preferably 100 to 150 sccm. In an embodiment of the present invention, the flow rate of the argon can be 120 sccm, and the flow rate of the nitrogen can be 60 sccm.
[0044] In the present invention, the conditions of the magnetron sputtering are preferably: the linear distance between the target and the substrate is preferably 100-200 mm, more preferably 130-160 mm; the pressure of the working gas is preferably 0.2-1.0 Pa, more preferably 0.5-0.8 Pa; the target current is preferably 5-12 A, more preferably 8-10 A; the deposition time is preferably 100-150 A, more preferably 120-130 A; the deposition temperature is preferably 303-573 K, more preferably 303 K or 573 K. In an embodiment of the present invention, the linear distance between the target and the substrate can be 140 mm; the pressure of the working gas can be 0.28-0.33 Pa; the target current can be 8 A, and the deposition time can be 120 min.
[0045] In the present invention, the magnetron sputtering device comprises a cavity and a workpiece rack and a titanium metal target arranged inside the cavity, wherein the workpiece rack and the titanium metal target are vertically placed inside the cavity; the substrate is placed on the workpiece rack, and a bias voltage is applied to the workpiece rack to realize the function of cleaning the substrate before coating. The titanium metal target is used for coating.
[0046] After obtaining the porous titanium nitride film, the present invention immerses the porous titanium nitride film in an aqueous solution of a molybdenum source and a sulfur source to obtain a titanium nitride film filled with a molybdenum disulfide precursor.
[0047] In the present invention, the aqueous solution of the molybdenum source and the sulfur source is an aqueous solution of ammonium tetrathiomolybdate; the concentration of the aqueous solution of ammonium tetrathiomolybdate is preferably 10 to 30 mg / mL, more preferably 15 to 25 mg / mL. In an embodiment of the present invention, the concentration of the aqueous solution of ammonium tetrathiomolybdate can be 20 mg / mL.
[0048] In the present invention, the immersion is preferably carried out under ultrasonic conditions, the number of ultrasonic treatments is preferably 2 to 5 times, more preferably 3 to 4 times; the frequency of each ultrasonic treatment is preferably 30 to 40 kHz, more preferably 40 kHz, and the time is preferably 40 to 60 min, more preferably 50 to 60 min. In an embodiment of the present invention, the number of ultrasonic treatments may be 3 times; the frequency of each ultrasonic treatment may be 40 kHz, and the time may be 60 min.
[0049] After obtaining the titanium nitride film filled with the molybdenum disulfide precursor, the present invention performs a reduction heat treatment on the titanium nitride film filled with the molybdenum disulfide precursor to obtain the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film.
[0050] In the present invention, the reduction heat treatment is preferably carried out under the condition of nitrogen and hydrogen, the flow rate of the nitrogen is preferably 40 to 80 sccm, more preferably 40 to 60 sccm; the flow rate of the hydrogen is preferably 20 to 40 sccm, more preferably 30 to 40 sccm. In an embodiment of the present invention, the flow rate of the nitrogen can be 80 sccm, and the flow rate of the hydrogen can be 40 sccm.
[0051] In the present invention, the reduction heat treatment temperature is preferably 300-450°C, more preferably 350-400°C; the time is preferably 40-80 min, more preferably 50-70 min. In an embodiment of the present invention, the reduction heat treatment temperature can be 400°C, and the time can be 60 min.
[0052] The present invention also provides a titanium nitride-based self-releasing molybdenum disulfide lubricating composite film prepared by the preparation method described in the above technical solution, comprising a porous titanium nitride film and molybdenum disulfide filled in the pore structure of the porous titanium nitride film;
[0053] The pore structure of the porous titanium nitride film is a submicron-level pore structure.
[0054] In the present invention, the average pore size of the porous titanium nitride film is preferably 30 to 200 nm.
[0055] In the present invention, the thickness of the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film is preferably 0.5 to 2 μm, and more preferably 1.0 to 1.5 μm.
[0056] The present invention also provides the application of the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film described in the above technical solution in the field of lubricating coatings. The present invention does not have any special limitation on the method of the application, and the method well known to those skilled in the art can be used.
[0057] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0058] Example 1
[0059] 304 stainless steel was selected as the substrate, and the size of the substrate was: a block of 20 mm×20 mm×2 mm;
[0060] The substrate was ultrasonically cleaned in acetone for 15 min and in anhydrous ethanol for 5 min, and then dried. The cleaned substrate was placed in a cavity, and the deposition angle of the substrate (the angle between the normal line of the substrate and the normal line of the titanium metal target) was adjusted to 85°, and the target-substrate distance (the straight-line distance between the target and the substrate) was adjusted to 140 mm. A rectangular titanium metal with a purity of 99.7% was used as a deposition target and placed vertically inside the chamber. The chamber temperature was set to 303 K, and the vacuum degree in the chamber was pumped to 8×10 -3 After the substrate was cleaned by glow discharge at a bias voltage of -1000 V for 30 min, the introduction rate of argon was adjusted to 400 sccm, the deposition target was turned on, and a current (8 A) was passed into the deposition target for 5 min to pre-deposit a titanium transition layer (160 nm); the introduction rate of argon was reduced to 120 sccm, and nitrogen was introduced into the cavity to deposit a titanium nitride film (the deposition time was 120 min, the flow rate of nitrogen was 60 sccm, and the vacuum degree was 2.8-3.3×10 -1 Pa), to obtain a porous titanium nitride film;
[0061] The porous titanium nitride film is immersed in an aqueous solution of ammonium tetrathiomolybdate with a concentration of 20 mg / mL (the immersion is carried out under ultrasonic conditions, the ultrasonic frequency is 40 kHz, the time is 60 min, and the number of ultrasonic times is 3 times) to obtain a titanium nitride film filled with a molybdenum disulfide precursor;
[0062] The titanium nitride film filled with molybdenum disulfide precursor was transferred to a tubular furnace, and subjected to reduction heat treatment (temperature 400°C, time 60 min) under the conditions of passing high-purity nitrogen (purity of 99.999%, flow rate of 80 sccm) and hydrogen (purity of 99.999%, flow rate of 40 sccm) to obtain a titanium nitride-based self-releasing molybdenum disulfide lubricating composite film with a thickness of 1.34 μm (denoted as TM1, including a porous titanium nitride film and molybdenum disulfide filled in the pore structure of the porous titanium nitride film; the average pore size of the porous titanium nitride film is 130 nm).
[0063] Example 2
[0064] 304 stainless steel was selected as the substrate, and the size of the substrate was: a block of 20 mm×20 mm×2 mm;
[0065] The substrate was ultrasonically cleaned in acetone for 15 min and in anhydrous ethanol for 5 min, and then dried. The cleaned substrate was placed in a cavity, and the deposition angle of the substrate (the angle between the normal line of the substrate and the normal line of the titanium metal target) was adjusted to 85°, and the target-substrate distance (the straight-line distance between the target and the substrate) was adjusted to 140 mm. A rectangular titanium metal with a purity of 99.7% was used as a deposition target and placed vertically inside the chamber. The chamber temperature was set to 573 K, and the vacuum degree in the chamber was pumped to 8×10 -3 After the substrate was cleaned by glow discharge at a bias voltage of -1000 V for 30 min, the argon gas introduction rate was adjusted to 400 sccm, the deposition target was turned on, and a current (8 A) was passed into the deposition target for 5 min to pre-deposit a titanium transition layer (163 nm); the argon gas introduction rate was reduced to 120 sccm, and nitrogen gas was introduced into the cavity to deposit a titanium nitride film (the deposition time was 120 min, the nitrogen gas flow rate was 60 sccm, and the vacuum degree was 2.8-3.3×10 -1 Pa), to obtain a porous titanium nitride film;
[0066] The porous titanium nitride film is immersed in an aqueous solution of ammonium tetrathiomolybdate with a concentration of 20 mg / mL (the immersion is carried out under ultrasonic conditions, the ultrasonic frequency is 40 kHz, the time is 60 min, and the number of ultrasonic times is 3 times) to obtain a titanium nitride film filled with a molybdenum disulfide precursor;
[0067] The titanium nitride film filled with molybdenum disulfide precursor was transferred to a tubular furnace, and subjected to reduction heat treatment (temperature 400°C, time 60 min) under the conditions of passing high-purity nitrogen (purity of 99.999%, flow rate of 80 sccm) and hydrogen (purity of 99.999%, flow rate of 40 sccm) to obtain a titanium nitride-based self-releasing molybdenum disulfide lubricating composite film with a thickness of 1.23 μm (denoted as TM2, including a porous titanium nitride film and molybdenum disulfide filled in the pore structure of the porous titanium nitride film; the average pore size of the porous titanium nitride film is 87 nm).
[0068] Example 3
[0069] 304 stainless steel was selected as the substrate, and the size of the substrate was: a block of 20 mm×20 mm×2 mm;
[0070] The substrate was ultrasonically cleaned in acetone for 15 min and in anhydrous ethanol for 5 min, and then dried. The cleaned substrate was placed in a cavity, and the deposition angle of the substrate (the angle between the normal line of the substrate and the normal line of the titanium metal target) was adjusted to 85°, and the target-substrate distance (the straight-line distance between the target and the substrate) was adjusted to 140 mm. A rectangular titanium metal with a purity of 99.7% was used as a deposition target and placed vertically inside the chamber. The chamber temperature was set to 303 K, and the vacuum degree in the chamber was pumped to 8×10 -3 After the substrate was cleaned by glow discharge at a bias voltage of -1000 V for 30 min, the introduction rate of argon was adjusted to 400 sccm, the deposition target was turned on, and a current (8 A) was passed into the deposition target for 5 min to pre-deposit a titanium transition layer (160 nm); the introduction rate of argon was reduced to 240 sccm, and nitrogen was introduced into the cavity to deposit a titanium nitride film (the deposition time was 120 min, the flow rate of nitrogen was 120 sccm, and the vacuum degree was 6 to 6.7 × 10 -1 Pa), to obtain a porous titanium nitride film;
[0071] The porous titanium nitride film is immersed in an aqueous solution of ammonium tetrathiomolybdate with a concentration of 20 mg / mL (the immersion is carried out under ultrasonic conditions, the ultrasonic frequency is 40 kHz, the time is 60 min, and the number of ultrasonic times is 3 times) to obtain a titanium nitride film filled with a molybdenum disulfide precursor;
[0072] The titanium nitride film filled with molybdenum disulfide precursor was transferred to a tubular furnace and subjected to reduction heat treatment (temperature 400°C, time 60 min) under the conditions of passing high-purity nitrogen (purity of 99.999%, flow rate of 80 sccm) and hydrogen (flow rate of 40 sccm) to obtain a titanium nitride-based self-releasing molybdenum disulfide lubricating composite film with a thickness of 1.48 μm (denoted as TM3, including a porous titanium nitride film and molybdenum disulfide filled in the pore structure of the porous titanium nitride film; the average pore size of the porous titanium nitride film is 45 nm).
[0073] Comparative Example 1
[0074] 304 stainless steel was selected as the substrate, and the size of the substrate was: a block of 20 mm×20 mm×2 mm;
[0075] The substrate was ultrasonically cleaned in acetone for 15 min and in anhydrous ethanol for 5 min, and then dried. The cleaned substrate was placed in a chamber, and the deposition angle of the substrate (the angle between the normal line of the substrate and the normal line of the titanium metal target) was adjusted to 0°, and the target-substrate distance (the straight-line distance between the target and the substrate) was adjusted to 140 mm. A rectangular titanium metal with a purity of 99.7% was used as a deposition target and placed vertically inside the chamber. The chamber temperature was set to 303 K, and the vacuum degree in the chamber was pumped to 8×10 -3 After the reaction was completed, a high-purity argon gas (with a purity of 99.999%) was introduced at a rate of 800 sccm. The substrate was cleaned by glow discharge for 30 min under a bias voltage of -1000 V. The introduction rate of the argon gas was adjusted to 400 sccm, the deposition target was turned on, and a current (8 A) was introduced into the deposition target for 5 min to pre-deposit a titanium transition layer (160 nm). The introduction rate of the argon gas was reduced to 120 sccm, and nitrogen gas was introduced into the cavity to deposit a titanium nitride film (the deposition time was 120 min, the flow rate of the nitrogen gas was 60 sccm, and the vacuum degree was 2.8-3.3×10 -1 Pa), to obtain a titanium nitride film;
[0076] The porous titanium nitride film is immersed in an aqueous solution of ammonium tetrathiomolybdate with a concentration of 20 mg / mL (the immersion is carried out under ultrasonic conditions, the ultrasonic frequency is 40 kHz, the time is 60 min, and the number of ultrasonic times is 3 times) to obtain a titanium nitride film filled with a molybdenum disulfide precursor;
[0077] The titanium nitride film filled with molybdenum disulfide precursor is transferred to a tubular furnace and subjected to reduction heat treatment (temperature 400°C, time 60 min) under the conditions of passing high-purity nitrogen (purity of 99.999%, flow rate of 80 sccm) and hydrogen (flow rate of 40 sccm) to obtain the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film (denoted as TM3, including titanium nitride film and molybdenum disulfide).
[0078] Comparative Example 2
[0079] 304 stainless steel was selected as the substrate, and the size of the substrate was: a block of 20 mm×20 mm×2 mm;
[0080] The substrate was ultrasonically cleaned in acetone for 15 min and in anhydrous ethanol for 5 min, and then dried. The cleaned substrate was placed in a cavity, and the deposition angle of the substrate (the angle between the normal line of the substrate and the normal line of the titanium metal target) was adjusted to 45°, and the target-substrate distance (the straight-line distance between the target and the substrate) was adjusted to 140 mm. A rectangular titanium metal with a purity of 99.7% was used as a deposition target and placed vertically inside the chamber. The chamber temperature was set to 303 K, and the vacuum degree in the chamber was pumped to 8×10 -3 After 1000 Pa, high-purity argon (purity of 99.999%) was introduced at a rate of 800 sccm. Under a bias voltage of -1000 V, the substrate was cleaned by glow discharge for 30 minutes. Then, the introduction rate of argon was adjusted to 400 sccm, the deposition target was turned on, and a current (8 A) was introduced into the deposition target for 5 minutes to pre-deposit a titanium transition layer (158 nm). The introduction rate of argon was reduced to 120 sccm, and nitrogen was introduced into the cavity to deposit a titanium nitride film (the deposition time was 120 minutes, the flow rate of nitrogen was 60 sccm, and the vacuum degree was 2.8 to 3.3 × 10 -1 Pa), to obtain a titanium nitride film;
[0081] The porous titanium nitride film is immersed in an aqueous solution of ammonium tetrathiomolybdate with a concentration of 20 mg / mL (the immersion is carried out under ultrasonic conditions, the ultrasonic frequency is 40 kHz, the time is 60 min, and the number of ultrasonic times is 3 times) to obtain a titanium nitride film filled with a molybdenum disulfide precursor;
[0082] The titanium nitride film filled with molybdenum disulfide precursor is transferred to a tubular furnace, and subjected to reduction heat treatment (temperature 400°C, time 60 min) under the conditions of passing high-purity nitrogen (purity of 99.999%, flow rate of 80 sccm) and hydrogen (flow rate of 40 sccm) to obtain the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film (denoted as TM4, including titanium nitride film and molybdenum disulfide, the titanium nitride film has a porous structure, but the pore size is worse than that of Example 2, about 43 nm).
[0083] Test Case
[0084] Figure 1 The surface SEM image (a) and the cross-sectional SEM image (c) of the dense titanium nitride film described in Comparative Example 1 and the surface SEM image (b) and the cross-sectional SEM image (b) of the porous titanium nitride film described in Example 2 are shown in FIG. Figure 1 It can be seen that, compared with the titanium nitride film deposited at a non-oblique angle (the dense titanium nitride film described in Comparative Example 1), the surface morphology of the titanium nitride film deposited at an oblique angle (the porous titanium nitride film described in Example 2) changes from a dense structure to a porous structure, and the cross-section of the titanium nitride film changes from a vertically grown bead-like structure to an inclined columnar growth;
[0085] Figure 2 The friction coefficient curve of the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film described in Example 2 when the relative humidity changes from 20% to 70%, Figure 3 The friction coefficient curve of the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film described in Comparative Example 1 when the relative humidity is changed from 20% to 70%; the test conditions are: the rotation radius is 4mm, the load is 2N, the diameter of the grinding ball (material silicon nitride) is 8mm, and the rotation speed is 200r / min; Figure 2It can be seen that in the friction test experiment, the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film described in Example 2 has a friction coefficient of 0.05 in a 20% relative humidity environment, and a friction coefficient of 0.2 in a 70% relative humidity environment, and can still return to a lower friction coefficient after experiencing multiple environmental humidity changes (the main reason is that molybdenum disulfide is a solid lubricating phase, which has a lower friction coefficient at 20% relative humidity. When it returns to 20% relative humidity after experiencing multiple environmental changes during the friction process, the molybdenum disulfide stored in the coating pores can be released to the friction contact surface, thereby reducing the friction coefficient); while the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film described in Comparative Example 1 has a friction coefficient of 0.05 in a 20% relative humidity environment, and a friction coefficient of 0.2 in a 70% relative humidity environment, but after experiencing an environmental change, the friction coefficient gradually increases and decreases, and finally increases to 0.7. It can be seen that the present invention realizes the introduction of molybdenum disulfide into the pores of the porous titanium nitride film, and can continuously release molybdenum disulfide in an environment where the relative humidity of the environment changes, and ultimately can maintain a relatively low friction coefficient after experiencing multiple environmental changes.
[0086] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a titanium nitride-based self-releasing molybdenum disulfide lubricating composite film, characterized in that: The following steps are involved: A porous titanium nitride film is prepared on the surface of a substrate by magnetron sputtering with titanium metal as a target; the angle between the normal line of the substrate and the normal line of the target is 80-89°; Soaking the porous titanium nitride film in an aqueous solution of a molybdenum source and a sulfur source to obtain a titanium nitride film filled with a molybdenum disulfide precursor; The titanium nitride film filled with the molybdenum disulfide precursor is subjected to reduction heat treatment to obtain the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film.
2. The preparation method according to claim 1, characterized in that During the magnetron sputtering process, the working gases are argon and nitrogen.
3. The preparation method according to claim 2, characterized in that: The conditions of the magnetron sputtering are: the straight-line distance between the target material and the substrate is 100-200 mm, the pressure of the working gas is 0.2-1.0 Pa, the flow rate of argon is 100-400 sccm, the flow rate of nitrogen is 50-200 sccm, the target current is 5-12 A, the deposition time is 100-150 min, and the deposition temperature is 303-573 K.
4. The preparation method according to claim 1, characterized in that: The aqueous solution of the molybdenum source and the sulfur source is an aqueous solution of ammonium tetrathiomolybdate; The concentration of the aqueous solution of ammonium tetrathiomolybdate is 10 to 30 mg / mL.
5. The preparation method according to claim 1 or 4, characterized in that: The immersion is carried out under ultrasonic conditions; The number of ultrasonic treatments is 2 to 5 times; the duration of each ultrasonic treatment is 40 to 60 minutes.
6. The preparation method according to claim 1, characterized in that: The reduction heat treatment is carried out under the condition of nitrogen and hydrogen; The flow rate of the nitrogen gas is 40 to 80 sccm, and the flow rate of the hydrogen gas is 20 to 40 sccm.
7. The preparation method according to claim 1 or 6, characterized in that: The reduction heat treatment is carried out at a temperature of 300 to 450° C. and for a time of 40 to 80 minutes.
8. The preparation method according to claim 1, characterized in that: Before preparing the porous titanium nitride film, the method further comprises preparing a titanium transition layer on the surface of the substrate.
9. The titanium nitride-based self-releasing molybdenum disulfide lubricating composite film prepared by the preparation method according to any one of claims 1 to 8, characterized in that: It includes a porous titanium nitride film and molybdenum disulfide filled in the pore structure of the porous titanium nitride film; The pore structure of the porous titanium nitride film is a submicron-level pore structure.
10. Use of the titanium nitride-based self-releasing molybdenum disulfide lubricating composite film according to claim 9 in the field of lubricating coatings.